2017
DOI: 10.24200/sci.2017.4448
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating demand, orders, lead time, and pricing decisions for reducing bullwhip effect in supply chains

Abstract: The purpose of this paper is to mitigate bullwhip effect (BWE) in a supply chain (SC). Four main contributions are proposed. The first one is to reduce BWE through considering its multiple causes (demand, pricing, ordering, and lead time) simultaneously. The second one is to model demands, orders, and prices dynamically for reducing BWE.Demand and prices have mutual effect on each other dynamically over time. In other words, a time series model is used in a game theory method for finding the optimal prices in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Dalam siklus perdagangan, distributor dituntut untuk melakukan distribusi barang dengan baik agar dapat mencegah kekosongan atau kelebihan stok pada pihak konsumen. Dimana tingkat kepuasan konsumen terhadap pelayanan distributor diukur apabila produk yang di distribusikan tiba tepat waktu, jumlah yang sesuai dan dengan kualitas yang baik [2] [3].…”
Section: Pendahuluanunclassified
“…Dalam siklus perdagangan, distributor dituntut untuk melakukan distribusi barang dengan baik agar dapat mencegah kekosongan atau kelebihan stok pada pihak konsumen. Dimana tingkat kepuasan konsumen terhadap pelayanan distributor diukur apabila produk yang di distribusikan tiba tepat waktu, jumlah yang sesuai dan dengan kualitas yang baik [2] [3].…”
Section: Pendahuluanunclassified
“…Gamasaee and Fazel Zarandi [40] investigated the impact of joint demand, orders, lead time and pricing decisions on reducing bullwhip effect. Their paper results show significant reduction in bullwhip effect.…”
Section: Bullwhip Effectmentioning
confidence: 99%
“…Yoo (2014) explored the connection between a return mechanism and commodity's quality in presence of a decentralized supply network and concluded that improving commodity's quality directly influences the amount of commodity's returns. In addition, there are some researches executed in this area to examine price decisions with different circumstances like Taleizadeh et al (2015b), Dan et al (2016), Jingxian et al (2017), Noori-daryan et al (2018, Mokhlesian and Zegordi (2018), Gamasaee and Fazel Zarandi (2018).…”
Section: Literature Reviewmentioning
confidence: 99%